Dietary intake according to the evolution of the resting metabolic rate and body composition of an elite Olympic athlete over a macrocycle: a case study - Saftel, M. A.; Leonte, N.; Maftei, A.; Moanta, A. D. (Applied Sciences, 2025)
Monitoring physiological parameters is vital for tracking swimmers` progress and performance. This study examines an elite male swimmer`s nutrition during his preparation for the 2024 Paris Olympics, considering his metabolic rate and body composition. His resting energy needs (2905 ± 407.99 kcal/day) were measured using indirect Cosmed K5, calorimetry, and body composition determined through skinfold measurements. Nutrition plans were developed using software, varying with his training intensity—providing 2910 ± 379 kcal/day on rest days, and 4238 ± 562 kcal/day on intense days. The analysis of the correlations between key variables revealed strong and diverse interactions among anthropometric, metabolic data, and energy substrates. Thus, weight exhibited a very strong positive correlation with lean mass (FFM), indicating that higher weight is associated with increased lean mass. Conversely, the moderate correlation between weight and body fat percentage suggests a weaker association. The amount of skin folds accurately reflects the body fat percentage. Ensuring that a high-energy dietary intake aligned with his actual needs throughout the season was crucial for sustaining performance. Experimenting with fueling and recovery tactics during smaller competitions enabled the athlete to meet energy and nutrient demands at the elite level.